2021
DOI: 10.1097/inf.0000000000003147
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Antibiotic Nonsusceptibility in Gram-negative Urinary Tract Infection in Children With Risk Factors Occurring in the Preceding Month

Abstract: Background: Choosing an empiric treatment for urinary tract infections (UTIs) requires epidemiologic data on antibiotic nonsusceptibility (ANS) rates, and risk factors for UTI and ANS in the individual patient. We assessed ANS in community-acquired UTI, and its association with risk factors exposure (previous antibiotic treatment, UTI and hospital visit) <1 month or 1-11 months before the current UTI episode. Methods: This was a retrospective, cohort study. Children <2 years with hospital visits and a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…These findings are important and may assist physicians in choosing an appropriate empiric treatment for UTI. 33 Our investigation clearly shows that there is a significant increase in trimethoprim and ciprofloxacin resistance among E. coli isolates taken from patients with UTI in our study area, which makes its empirical treatment challenging. The reported rates of resistance among the most frequent microorganisms in numerous research articles may vary depending on whether the study sample consists primarily of outpatients with uncomplicated UTI or patients with complicated infections.…”
Section: Discussionmentioning
confidence: 69%
“…These findings are important and may assist physicians in choosing an appropriate empiric treatment for UTI. 33 Our investigation clearly shows that there is a significant increase in trimethoprim and ciprofloxacin resistance among E. coli isolates taken from patients with UTI in our study area, which makes its empirical treatment challenging. The reported rates of resistance among the most frequent microorganisms in numerous research articles may vary depending on whether the study sample consists primarily of outpatients with uncomplicated UTI or patients with complicated infections.…”
Section: Discussionmentioning
confidence: 69%
“…36 Another study examined antibiotic susceptibility patterns among various pathogens ( K. pneumoniae , Enterobacter spp., and E. coli ) causing inpatient UTIs among children and reported a higher risk of resistance to some antibiotics (e.g., ampicillin, TMP/SMX, cephalosporins) among Bedouin versus Jewish children, but no significant difference for other antibiotics (e.g., nitrofurantoin, meropenem, amikacin). 39 Another study reported a higher risk of UTI caused by ESBL-producing vs non-ESBL-producing bacteria in Arab children than Jewish children. 52 In a prospective cohort study of 223 adults with UTIs caused by E. coli , P. aeruginosa , or Enterococcus faecium , no difference in antibiotic susceptibility patterns was observed between Bedouin versus non-Bedouins adults.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 54 included studies, 3,12–69 42 (78%) described infections and 12 (22%) described colonization with at least one of the pathogens of interest ( Table 1 ). 13,18,26,33,37,43,45,47,50,51,53–55,57 Most studies were from the USA (n=42), 3,14–17,20,21,21,23–28,30–33,37,38,40–42,44–51,53–63,67–69 although studies from Israel (n=5), 13,29,34,36,39,52 New Zealand (n=4), 12,43,64–66 Australia (n=2), 19,35 and Brazil (n=1) 18 were also identified ( Figure 1 ). Studies of infection most often included patients with skin and soft tissue infection (SSTI) caused by S. aureus or urinary tract infection (UTI) caused by E. coli or other Enterobacterales, while other infections like community-acquired pneumonia (CAP) were described more rarely.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, otros microorganismos, como Staphylococcus saprophyticus, Klebsiella pneumoniae y Proteus mirabilis, también pueden estar involucrados. (5,6,7) Comprender qué patógenos están implicados y cómo interactúan con el tracto urinario es esencial para desarrollar estrategias de prevención y tratamiento adecuadas. (8) Esta información es fundamental para el desarrollo de medidas preventivas efectivas, la mejora de los protocolos de tratamiento y la reducción de la carga global de las infecciones urinarias en la población.…”
Section: Introductionunclassified